Prinsip Kejujuran Dalam Usaha - Qorina, Ulfa; Ridwan, Saleh; Lutfi, Muhtar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The principle of honesty in business is an important foundation that influences various operational and strategic aspects of the company. Honesty includes transparency in communications, disclosure of financial information, and integrity in all business actions. Implementing these principles builds a positive reputation and trust from customers, creates a healthy work environment, and encourages effective internal and external collaboration. In practice, honesty facilitates strong relationships with stakeholders such as investors and business partners. Trust built from honesty helps companies gain long-term support and cooperation, which is essential for business sustainability. In addition, companies that operate honestly tend to be better able to avoid legal and ethical risks, and are better prepared to face market challenges. Companies that uphold honesty do not only focus on short-term profits but are also committed to creating sustainable added value for all parties involved. Thus, honesty in business is the key to achieving long-term success and building a solid foundation for sustainable business growth.